Oxygen sensing coordinates photomorphogenesis to facilitate seedling survival - Abbas, Mohamad; Berckhan, Sophie; Rooney, Daniel J.; Gibbs, Daniel J.; Vicente Conde, Jorge; Sousa Correia, Cristina; Bassel, George W.; Marín-de la Rosa, Nora; León, José; Alabadí, David; Blázquez, Miguel A.; Holdsworth, Michael J. (Elsevier (Cell Press), 2015)
Successful emergence from the soil is essential for plant establishment in natural and farmed systems. It has been assumed that the absence of light in the soil is the preeminent signal perceived during early seedling development, leading to a distinct morphogenic plan (skotomorphogenesis) [1], characterized by traits providing an adaptive advantage until emergence and photomorphogenesis. These traits include suppressed chlorophyll synthesis, promotion of hypocotyl elongation, and formation of a closed apical hook that protects the stem cell niche from damage [2, 3]. However, absence of light by itself is not a sufficient environmental signal for early seedling development [4, 5]. Reduced oxygen levels (hypoxia) can occur in water-logged soils [6-8]. We therefore hypothesized that below-ground hypoxia may be an important, but thus far undiscovered, ecological component regulating seedling development. Here, we show that survival and establishment of seedlings following darkness depend on their ability to sense hypoxia, through enhanced stability of group VII Ethylene Response Factor (ERFVII) transcription factors. Hypoxia is perceived as a positive environmental component in diverse taxa of flowering plants, promoting maintenance of skotomorphogenic traits. Hypoxia greatly enhances survival once light is perceived, while oxygen is necessary for the subsequent effective completion of photomorphogenesis. Together with light perception, oxygen sensing therefore allows an integrated response to the complex and changing physical microenvironment encountered during early seedling growth. We propose that plants monitor the soil's gaseous environment after germination, using hypoxia as a key external cue to protect the stem cell niche, thus ensuring successful rapid establishment upon emergence above ground.